Course Project in Mobile Computing â€“ An Experiential Learning - Desai, Shrinivas D.; Narayankar, Prashant (Journal of Engineering Education Transformations, 2018)
As a predominant technology among our student bodies (with smart phones and tablets), along with the growing market for Android or iPhone developers, students are yearning for understanding the computations that happen at the back-end. In this paper, a case study of a project in â€œMobile computingâ€ course is presented. Students were encouraged to develop new applications to retrieve the back end data such as SIM information, Nearest Tower Information and Protocol stack employed during Internet browsing. The main objective the course project is to strengthen the theoretical concepts in the class by experimenting with real-time mobile system. Assessment of student’s â€œunderstanding levelâ€ prior to and after the course project is recorded. Analysis of the assessment data showed that the students developed a good level of understanding of the underlying wireless and mobile communication networks and their technical features, and were able to map the theoretical concepts learnt in class with practical applications. The project objectives of improving programming skills and developing mobile apps are found to complement the course outcomes.